THE SYMBOLIC MEANING OF THE SAWER TRADITION IN SUNDANESE TRADITIONAL WEDDINGS IN BERINGIN JAYA VILLAGE - niswatin uliah; Gusti Ketut Alit Suputra; Arum Pujining Tyas; Ida Nuraeni; Julia Marfuah (Universitas Muhammadiyah Makassar, 2026)
The Sawer tradition is an important stage in Sundanese traditional wedding ceremonies that incorporates various verbal and nonverbal symbols as a medium for conveying advice, prayers, and cultural values to newlywed couples. However, the symbolic meanings embedded in this tradition are not fully understood by the community, including some members of the Sundanese ethnic group themselves. This study aims to describe and analyze the forms and meanings of verbal and nonverbal symbols in the Sawer tradition of Sundanese wedding ceremonies in Beringin Jaya Village, Bumi Raya District, Morowali Regency. The study employed a descriptive qualitative approach using Ferdinand de Saussure’s semiotic theory. Data were collected through observation, interviews, and documentation and analyzed using the Miles and Huberman interactive model, which includes data collection, data reduction, data display, and conclusion drawing and verification. The findings reveal that verbal symbols in the Sawer tradition are expressed through four categories of ritual songs: the opening song, the song for the groom, the song for the bride, and the closing song. These symbols represent religiosity, responsibility, commitment, fidelity, cooperation, harmony, and divine blessing. Meanwhile, the nonverbal symbols, including yellow rice, candies, money and coins, and an umbrella, symbolize prosperity, harmony, economic well-being, protection, and family happiness. The findings indicate that the Sawer tradition functions as a medium for transmitting cultural, moral, social, and religious values and plays a significant role in preserving the cultural identity of Sundanese migrant communities.